FORMATION OF THE SOCIAL CAPITAL BY ITS DIMENSIONS IN RURAL AREAS OF ERZURUM PROVINCE IN TURKEY - A. Keskin; ^. Kele_ (Journal of Animal and Plant Sciences, 2018)
In this study, the formation of and the factors influencing social capital, the link between the rural lifestyle and the social capital were investigated. The levels of the social capital by their dimensions in rural areas were determined. The main material of the study is comprised of the cross sectional data, obtained from surveys conducted with random sampling method in 2016 from the counties and villages outside the Erzurum City Center. In the study, which utilized the Structural Equation Model, LISREL 8.72 software packages were used. The results of the study show that the elements that can be considered as the sources of social capital have become subjects that restrict social mobility and the cooperation instead of having a capitalistic value due to the fact that such elements are not supported by a sufficient and effective tradition of the society. The social capital, with its dimensions can only be realized in rural areas in a strong manner to the extent that the norms as well as ethnic and religion based strong social bonds play a unifying and infusive role instead of being a source of discrimination and marginalization in the society. the actors that are in such networks. Whiteley (2000)
Keywords: Social capital; dimension; rural development; structural equation model; Turkey.